2010
DOI: 10.1007/s10230-010-0127-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Geochemical Behaviour of Waste Rock with Low Acid Generating Potential Using Laboratory Kinetic Tests

Abstract: Prediction of contaminated neutral drainage using laboratory kinetic tests designed for acid mine drainage prediction is challenging because of the low metal concentrations generated by low sulfide oxidation rates. Fresh and weathered samples from the Tio mine waste rock piles were submitted to humidity cell tests. The waste rocks were demonstrated to be non-acid generating in the long term, as interpreted by conservative oxidation-neutralization curves. The results demonstrate that even though the main neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 86 publications
3
27
0
Order By: Relevance
“…25 years old) Tio mine waste rocks suggested that the waste rocks are not acid-generating in the long term (Pepin 2009;Plante et al 2010a). The geochemical behaviours of the main minerals composing the Tio waste rocks (ilmenite, plagioclase, and pyroxenes) are well described in the literature and are summarized below.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…25 years old) Tio mine waste rocks suggested that the waste rocks are not acid-generating in the long term (Pepin 2009;Plante et al 2010a). The geochemical behaviours of the main minerals composing the Tio waste rocks (ilmenite, plagioclase, and pyroxenes) are well described in the literature and are summarized below.…”
mentioning
confidence: 96%
“…In order to validate that the response of the two types of tests were similar for the Tio mine waste rocks, weathering cell tests were performed on the same Tio mine waste rocks that were studied in the humidity cells (Plante et al 2010a). Weathering cells were also performed on purified mineral fractions of ilmenite and plagioclase prepared from the Tio mine waste rock (Plante et al 2010b).…”
mentioning
confidence: 99%
“…The use of a concentrate to mimic the behavior of REE in waste material is done in order to amplify the geochemical responses that could be obtained from mine wastes, and make measurement and interpretation more robust. This methodology was successfully applied in another context [52]. Consequently, the interpretation of the weathering cell data will not be investigated further; the interested readers are invited to consult [45].…”
Section: Implications To the Prediction Of The Geochemical Behavior Amentioning
confidence: 99%
“…However , many toxic metals, such as As, Co, Ni, Sb and Zn, are soluble at near -neutral pH and can potentially contami nate mine effluents, even without acidic conditions (Plante et al 2011). Thus, depending on the neutralization capacity of the mining wastes, tailings, and ore host rocks, the production of neutral mine waters may be of environmental concern.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, depending on the neutralization capacity of the mining wastes, tailings, and ore host rocks, the production of neutral mine waters may be of environmental concern. Although less well documented, neutral mine drainage may also constitute a significant environmental problem due to the mobili zation of metalloids such as As, Sb, Se, and metals such as Cd, Pb, and Zn (Heikkinen et al 2009;Plante et al 2011;J ang and Kwon 2011). The geochemistr y of the mineral -water interaction is dependent on the ore and gangue minerals, local water chemistr y, and geologic setting.…”
Section: Introductionmentioning
confidence: 99%